(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2022)
In this article, I aim to provide an overview of the Welcoming Association, my own experiences and the causes of forced human displacement. I was born to a working-class family in 1960s Tigray, Northern Ethiopia. My father died when I was nine years old and I was brought up by my courageous mother, supported by my uncles. Throughout my secondary school education, I was brainwashed by Marxism, Leninism and Maoism. I was taught about the evolution of systems from primitive communal society to 20th century communist systems in my mother tongue, Tigrinya.